Heat illness in military populations: asking the right questions for research. Issue 2 (3rd January 2014) - Stacey, Mike; Woods, D; Ross, D; Wilson, D
Abstract : Reports of death and injury in military populations due to exertional heat illness (EHI) and its most severe form, exertional heat stroke, date from antiquity. Yet, understanding of why one soldier may succumb to EHI, while those around him do not, is incomplete. This paper sets out research questions in support of the health of military populations who may experience exertional heat stress. The mechanisms by which excess body heat arises and is dissipated are outlined and the significance of core temperature measurement during exercise is discussed. Known risk factors for EHI are highlighted and new approaches for identifying individual vulnerability to EHI are introduced. A better understanding of the underlying pathophysiology may allow the effective use of biomarkers in future risk stratification and identification of EHI, allied to emerging genetic technologies. The thermal burden associated with states of dress and personal protection of Service personnel in their worldwide duties should be a focus of research as new equipment is introduced. At all times, the discerning use of existing guidance by Commanders on the ground will remain a mainstay of preventing EHI.